2006
DOI: 10.1097/01.rhu.0000231381.21179.e6
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Musculoskeletal Manifestations in Polymyalgia Rheumatica

Abstract: Fifty-one percent of the patients with PMR presented distal musculoskeletal manifestations, with peripheral synovitis being the most frequent one. Patients with PMR with peripheral synovitis did not represent a high-risk subgroup with more severe disease. Seven patients who developed criteria for seronegative RA within the first year of follow up had presented statistically significant persistent synovitis compared with those who continued as PMR and also showed a smaller initial decrease in mean ESR after ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 24 publications
0
15
0
2
Order By: Relevance
“…The prognostic value of peripheral arthritis was investigated by seven studies (n=645, LoB 2–6/8) 24 35 38 45 46 55 57. The presence of peripheral arthritis was associated with a higher risk of relapse according to one study (n=177, LoB 5/8),55 whereas three studies (n=207, LoB 5–6/8) did not confirm this observation 24 35 55…”
Section: Resultsmentioning
confidence: 99%
“…The prognostic value of peripheral arthritis was investigated by seven studies (n=645, LoB 2–6/8) 24 35 38 45 46 55 57. The presence of peripheral arthritis was associated with a higher risk of relapse according to one study (n=177, LoB 5/8),55 whereas three studies (n=207, LoB 5–6/8) did not confirm this observation 24 35 55…”
Section: Resultsmentioning
confidence: 99%
“…Baseline factors that were associated with a higher relapse rate and/or prolonged therapy in PMR studies were: female sex (38,47), high erythrocyte sedimentation rate (ESR) (.40 mm/hour) (47)(48)(49)(50)(51)53) and peripheral inflammatory arthritis (54). A number of studies, however, failed to demonstrate association between these factors and relapse (48)(49)(50)(51)54,(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78). 4 Use the minimum effective dose out of a range of 12.5-25 mg prednisone equivalent daily: a high risk of relapse/prolonged therapy favors a higher dose, while a high risk of side effects favors a lower dose.…”
Section: Resultsmentioning
confidence: 99%
“…Carpal tunnel syndrome in PMR has also been noted. 15 Ceccato et al 16 showed that 39% of patients who had peripheral synovitis presented with pitting edema (5%), carpal tunnel syndrome (5%), and distal tenosynovitis (1.3%). In our 41 patients with PMR, four patients (9.8%) developed distal arthritis and 50% of distal arthritis was knee arthritis.…”
Section: Discussionmentioning
confidence: 99%